A meta-analysis of genome-wide association studies of asthma in Puerto Ricans. Issue 5 (2nd May 2017) - Yan, Qi; Brehm, John; Pino-Yanes, Maria; Forno, Erick; Lin, Jerome; Oh, Sam S.; Acosta-Perez, Edna; Laurie, Cathy C.; Cloutier, Michelle M.; Raby, Benjamin A.; Stilp, Adrienne M.; Sofer, Tamar; et al.
Puerto Ricans are disproportionately affected with asthma in the USA. In this study, we aim to identify genetic variants that confer susceptibility to asthma in Puerto Ricans. We conducted a meta-analysis of genome-wide association studies (GWAS) of asthma in Puerto Ricans, including participants from: the Genetics of Asthma in Latino Americans (GALA) I-II, the Hartford–Puerto Rico Study and the Hispanic Community Health Study. Moreover, we examined whether susceptibility loci identified in previous meta-analyses of GWAS are associated with asthma in Puerto Ricans. The only locus to achieve genome-wide significance was chromosome 17q21, as evidenced by our top single nucleotide polymorphism (SNP), rs907092 (OR 0.71, p=1.2×10 −12 ) at IKZF3 . Similar to results in non-Puerto Ricans, SNPs in genes in the same linkage disequilibrium block as IKZF3 ( e.g. ZPBP2, ORMDL3 and GSDMB ) were significantly associated with asthma in Puerto Ricans. With regard to results from a meta-analysis in Europeans, we replicated findings for rs2305480 at GSDMB, but not for SNPs in any other genes. On the other hand, we replicated results from a meta-analysis of North American populations for SNPs at IL1RL1, TSLP and GSDMB but not for IL33 . Our findings suggest that common variants on chromosome 17q21 have the greatest effects on asthma in Puerto Ricans. Common allelic variants on chromosome 17q21 have the greatest effects on asthma in Puerto Ricans, a high-risk group http://ow.ly/OtZq3084XV1